New Metatherian Mammal from the Early Eocene of Antarctica - Goin, Francisco Javier (2020)
A new Paleogene metatherian from locality IAA 1/90, Marambio (Seymour) Island in the Antarctic Peninsula is described. Pujatodon ektopos, gen. et sp. nov., is recognized on the basis of a tiny lower left molar recovered from early Eocene (late Ypresian) levels of the Cucullaea I Allomember, La Meseta Formation. The tooth is characterized by its small size, bunoid aspect, short trigonid with closely set paraconid and metaconid, wide and long talonid, the development of an incipient cingulid at the labial base of the crown between the trigonid and talonid, and an expanded posterior cingulid. Body mass estimations for the new taxon range from 83.13 to 153.15 g. Its enamel microstructure shows the earliest evidence among metatherians of aligned prisms, as well as of interprismatic sheets of matrix. The analysis of other parameters, like body mass, molar morphometric index, and wear facets, suggests that the molars of Pujatodon were primarily adapted to the processing of fruits, nuts, seeds, and/or hard insects. Several features suggest the allocation of this specimen among basal polydolopimorphians (Prepidolopidae or, more probably, Glasbiidae). The discovery of the specimen MLP 14-I-10-20 could offer new insights on the origins and early diversification of Australidelphian marsupials in southern (and northern?) continents. It also adds significant information on the diversity of Antarctic Paleogene mammals, their evolution, habits, and historical biogeography.